ANALYSIS OF THE DEWINGING PROCESS ON SCOTS PINE SEEDS WITH SMALL-SIZED DEWINGER (Innovation in Woodworking Industry and Engineering design, 2026)
In recent years, in Bulgaria there is a tendency to reduce the yield of seeds of conifers. This implies a more efficient use of machines with less power and performance. The forest seed producing stations in the country are equipped with small-sized dewingers "Unitech", but at this stage we still lack research and data to work with seeds of Scots pine. In the present work, a study has been conducted and an analysis has been made on the dewinging process of the Scots pine seeds (Pinus silvestris L.) with a small-sized paddle dewinger "Unitech". As a result, functional dependencies have been identified, which express the relationship of the rotation speed of the working bodies and the duration of the process on the quality of the harvested seeds and the operating performance of the machine. On this basis, the optimal process parameters have been established and specific modes of dewinging of Scots pine seeds have been proposed. The obtained results have an applied science nature in the field of forest seed production and the design of machines for dewinging of seeds.